Improving forensic mental health care for Aboriginal Australians – Challenges and opportunities - Durey, Angela; Wynaden, Dianne; Ali, Mohammed; Barr, L. (Wiley-Blackwell Publishing Asia, 2014)
Mental disorders constitute a major burden of disease in Aboriginal and Torres Strait Islander(hereafter Aboriginal) Australians who are also over-represented in the prison system. A legacy of colonisation compounds such prevalence and is further exacerbated by the persistence of racial discrimination and insensitivity across many sectors including health. This research completed in a Western Australian forensic mental health setting identifies non-Aboriginal health professionals’ support needs to deliver high quality, culturally safe care to Aboriginal patients. Data were collected from health professionals using an online survey and ten semi-structured interviews. Survey and interview results found ongoing education was needed for staff to provide culturally safe care where Aboriginal knowledge beliefs and values were respected. Findings also support previous research linking Indigenous health providers to improved health outcomes for Aboriginal patients. In a colonised country like Australia, education programs that critically reflect on power relations privileging white Anglo-Australian cultural dominance and subjugating Aboriginal knowledge, beliefs and values are important to identify factors promoting or compromising care of Aboriginal patients and developing a deeper understanding of ‘cultural safety’ and its clinical application. Organisational commitment is needed to translate findings to support non-Aboriginal health professionals deliver high quality care to Aboriginal patients that is respectful of cultural differences.